Free-will, responsibility and punishment - Haksar, V; Haksar, Vinit (1968)
﻿ One of the purposes of this thesis is to try to examine the concepts of mental sickness and responsibility (and some other related concepts) and see whether or not they can be defended against some of the criticisms that have been made against them. It has, for instance, been argued that the concept mental sickness is culture relative in a bad sense. If this criticism is valid, then we cannot be justified in saying that mental sickness has impaired a person's responsibility. Another criticism that has been made is that arguments that use mental sickness to explain and excuse criminal behaviour are circular. Most of the criticisms that I have discussed are intended to be general, i.e. they are criticisms of the concept of mental disorder im general, not just of a particular kind of mental disorder. Thus though Lady Wootton says that arguments that try to explain the psychopath's anti-social behaviour are circular, she thinks (at least in her more radical moments) that the circular process prevails in other mental disorders as well (e.g. with mental defectives. See Social Science and Social Pathology, page 256 ff.). Similarly, the argument that different standards of mental defect prevail in different cultures, and that therefore there is something wrong with the concept of mental defect, is intended to be (at least in her more radical moments) a general one, i.e. it is intended to apply, mutatis mutandis against other kinds of mental disorders also. [Please see pdf. for full abstract.]